Ferroptosis in Cancer Progression: Role of Noncoding RNAs - Zuo, Ying-Bing; Zhang, Yin-Feng; Zhang, Rui; Tian, Jia-Wei; Lv, Xiao-Bing; Li, Rong; Li, Shu-Ping; Cheng, Meng-Die; Shan, Jing; Zhao, Zheng; Xin, Hui (International journal of biological sciences, 2022)
Ferroptosis is a novel form of programmed cell death, and it is characterized by iron-dependent oxidative damage, lipid peroxidation and reactive oxygen species accumulation. Notable studies have revealed that ferroptosis plays vital roles in tumor occurrence and that abundant ferroptosis in cells can inhibit tumor progression. Recently, some noncoding RNAs (ncRNAs), particularly microRNAs, long noncoding RNAs, and circular RNAs, have been shown to be involved in biological processes of ferroptosis, thus affecting cancer growth. However, the definite regulatory mechanism of this phenomenon is still unclear. To clarify this issue, increasing studies have focused on the regulatory roles of ncRNAs in the initiation and development of ferroptosis and the role of ferroptosis in progression of various cancers, such as lung, liver, and breast cancers. In this review, we systematically summarized the relationship between ferroptosis-associated ncRNAs and cancer progression. Moreover, additional evidence is needed to identify the role of ferroptosis-related ncRNAs in cancer progression. This review will help us to understand the roles of ncRNAs in ferroptosis and cancer progression and may provide new ideas for exploring novel diagnostic and therapeutic biomarkers for cancer in the future.